A FRAMEWORK FOR SMART EXPERIENCE DESIGN BASED ON ZERO-PARTY CUSTOMER EXPERIENCE DATA - Kim Yong Se (United Kingdom, 2025)
Data about customer experiences would be critical in smart product-service systems. Research is desired on how to establish a framework for Smart Experience Design based on customer experience data so that determining what kinds of customer data are needed and how these data are acquired effectively can be supported. This paper presents a framework and a method to design customer experience personalization services based on customer experience evaluation data obtained in real time and accumulated together with context data. Two illustrative cases are provided to demonstrate the validity of the framework of smart experience design based on customer experience data.
ICED23: The 24th International Conference on Engineering Design